METODE KETELADANAN DAN PEMBIASAAN DALAM PENANAMAN NILAI-NILAI DAN PEMBENTUKAN SIKAP PADA ANAK - Sitompul, Hafsah (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2016)
A powerful method and intensive education in instilling values and forming attitudes are exemplary and habituation. The most responsible institution in this case is the family. It is important to realize that every parent must be in shaping the moral, instilling faith and worship train children who are the responsibility of parents as the primary educators. Besides formal education institutions, teachers are as educators, parents also play a second role only to instill the values and shape attitudes in students